Suami Sebagai Penanggung Jawab Nafkah Keluarga: Analisis Struktural-Fungsional Talcott Parsons - Hidayatullah, Syarif; Rozak, Fakih Abdul (Al-Mizan (e-Journal), 2024)
Being responsible for providing income is an important role in the family which has a significant impact on the function and dynamics of the family, in this case, the husband plays an active role in playing the role of being responsible for providing income in the family.  This paper aims to examine the role of the husband as the person responsible for providing income in the family using Tarlott Parsons' structural-functional theory analysis.  This paper uses qualitative research methods through the sociological approach of Talcott Parsons' functional structural theory (AGIL).  The research results show that husbands have a functional and responsible role in earning a living for the family.  Of course, cooperation and good understanding are needed from each family member to create harmony and stability in the family.  The AGIL scheme in functional structural theory has proven useful in analyzing the husband's duties as the person responsible for providing support.  This scheme helps to understanding how husbands adapt to environmental changes, achieve their goals, integrate themselves with the family system, and maintain the values ​​and norms of the family and society. It is hoped that this paper can provide theoretical and practical contributions in understanding the role and responsibilities of husbands in earning a living to overcome various problems related to family livelihoods, such as poverty, social inequality, and family conflict.